Disputes Upon Sabah: Clans Claims and Malaysian Sovereignty - Haji Mohamed Anwar, Omar Din; Mat Zin, Mat Akib; Ohani, Haji Abdul Ghani (2014)
At the risk of appearing Malaysian-centric, this paper seeks to Malaysia's legitimacy in asserting validate the legitimacy for Malaysia to assert its sovereignty over North Borneo, now Sabah, on the grounds of primary legal documents. Namely, four grant treaty documents signed by the Sultan of Brunei Darussalam and the Sultan of Sulu, and Gustavus Baron von Overbeck and Alfred Dent Esquire as representatives of a British Company respectively in 1877 and 1878. According to those treaties, the Brunei Sultanate and the Sulu Sultan had granted the territories to Dent and von Overbeck. Accordingly, the British had the absolute right to cede those territories to whomever they wanted, and in that case it was to Malaysia, when Sabah joined Malaysia in 1963. The second part of this paper examines the claims advanced among the Sulu’s ruling house in the 20th century upon Sabah after the death of Dayang in 1947. Those ruling house groups are heretofore referred to as “clans.”